1985
DOI: 10.1111/j.1365-2109.1985.tb00304.x
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of anglers’records (trout and sea trout, Salmo trutta L., and salmon, Salmo salar L.)

Abstract: Abstract. This paper collates the results of five surveys which were made to determine the average catch of anglers not making a return at game fisheries. This pilot study shows that the average catch per licence/permit () may be estimated from the average and the proportion of unprompted returns, (mu) and (pu) respectively, by the empirical equation , for trout and sea trout, Salmo trutta L. Salmon, Salmo salar L., catcrl’rates may be best estimated from . Typical values for United Kingdom waters are tabulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In many areas managers do not have access to accurate angler returns such as those available on the R. Bush, but methodology for the accurate estimation of angling catches from partial reporting of returns has been explored (Small & Downham, 1985), and various degrees of success have been claimed. Uncertainties about how representative of total angling success partial returns are, must always be included in the calculations, usually on the basis of local knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In many areas managers do not have access to accurate angler returns such as those available on the R. Bush, but methodology for the accurate estimation of angling catches from partial reporting of returns has been explored (Small & Downham, 1985), and various degrees of success have been claimed. Uncertainties about how representative of total angling success partial returns are, must always be included in the calculations, usually on the basis of local knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to estimate the average catcb of anglers not submitting a return from parameters of the negative binomal catch distribution for a given fishery calculated from returns submitted (Small & Downham, 1985).…”
Section: What Can He Learnt From the Case Studies In The Present Study?mentioning
confidence: 99%
“…An alternative method of specifying σ 2 has its roots in the work of Curtis (1943) and Bartlett (1947), who showed that transformations to homogenize variance can be determined from the relationship between σ 2 and µ. Inasmuch as the σ 2 to µ relationship is seldom known, it is frequently inferred from regressions of s 2 on x (Green 1979, Taylor 1980, Taylor et al 1983). This practice is quite common in fisheries work because s 2 and x are often found to be highly correlated (Taylor 1953, Small and Downham 1985, Porch and Fox 1990, Lester et al 1991, Cyr et al 1992, Warwick and Clarke 1993, Welch and Ishida 1993, Dong and Restrepo 1996. However, the relationship between s 2 and x is largely spurious.…”
Section: Introductionmentioning
confidence: 99%